<div dir="ltr"><div class="gmail_extra"><div class="gmail_quote">On Sat, Apr 23, 2016 at 3:30 AM, Bill Cox <span dir="ltr"><<a href="mailto:waywardgeek@gmail.com" target="_blank">waywardgeek@gmail.com</a>></span> wrote:<br><blockquote class="gmail_quote" style="margin:0px 0px 0px 0.8ex;border-left-width:1px;border-left-style:solid;border-left-color:rgb(204,204,204);padding-left:1ex"><div dir="ltr"><div>Puzzle 3:<br></div><div><br></div><div>Find functions X(x, y) and Y(x, y) such that:</div><div><br></div><div><div>  X(x, y)^2 - Y(x, y)^2 = X((x^2 - y^2)/(2 - x^2 - y^2), 2xy/(x^2 + y^2))</div><div>  2X(x, y)Y(x, y) = Y(x^2 - y^2)/(2 - x^2 - y^2), 2xy/(x^2 + y^2))</div></div><div><br></div></div></blockquote><div><br></div><div>Note that if you restrain this to the circle, it works out:</div><div><br></div><div>    x^2 + y^2  = 1, X(x, y) = x, Y(x, y)  = y</div><div><br></div><div>This is a sub-case of an Edwards curve, with d = 0.  For d != 0, an alternate form of the equations is:</div><div><br></div><div><div><div>  X(x, y)^2 - Y(x, y)^2 = X((x^2 - y^2)/(1 - dx^2y^2), 2xy/(1 + dx^2y^2))</div><div>  2X(x, y)Y(x, y) = Y((x^2 - y^2)/(1 - dx^2y^2), 2xy/(1 + dx^2y^2))</div></div></div><div><br></div><div>Bill</div></div></div></div>